Stress tests and asset quality reviews of banks: A policy announcement tool - Lazzari, Valter; Vena, Luigi; Venegoni, Andrea (Journal of Financial Stability, 2017)
It is common in the supervision of banks to perform and disclose a simultaneous standardized assessment of their asset quality, organizational effectiveness, strategic viability and resilience to financial turmoil. By investigating the European Central Bank 2014 Comprehensive Assessment and the stock reactions of the banks to its findings, we find that this process provides limited assistance to the market in sorting good from troubled banks. Notwithstanding, the market adjusts to these findings, since it understands that they signal the stance of supervisory policy toward banking activities, which begets the level of regulatory risk and cost for the supervised banks.